EFEKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN SUMAMBU (Hyptis capitata Jacq.) PADA TIKUS PUTIH JANTAN (Rattus norvegicus L.) YANG DIINDUKSI DENGAN KARAGENAN - Mia Audina; Yuliet Yuliet; Khildah Khaerati (Biocelebes, 2018)
One of the medical plants that can be used as an anti-inflamation treatment is sumambu leaf (Hyptis capitata Jacq.). Most of people in binangga village, Subdistric of central Parigi, Regency of Parigi Moutong, have been used this sumambu leaf for deducting inflammation, swelling, and painful. The aimed of this research is to know the effectiveness of the anti-inflamation of Sumambu leaf (Hyptis capitata Jacq.) towards white male mouse (Rattus novergicus L.) which has been given carrageenan induction. The extract was made by using a maseration method using 96% ethanol liquid. The test of the effectiveness of anti-inflamation was divided into your treatments which each treatment was consist of five mice which have been given negative control  0.5% CMC-Na suspension ;100 mg/KgBW, 200 mg/KgBW, 300 mg/KgBW of sumambu leaf extract. After 60 minutes, 0.1 ml carregeenan has been injected using subplantar method at the paw of the mice. The inflamation volume measured using  pletysmometer for 6 hours.  The data collection was statistically analyzed by ANOVA (Analysis of variance) one direction and continued to Duncan test. The results of this research  showed that the three doses of sumambu extract which are ES 100 mg/KgBW, 200 mg/KgBW, 300 mg/KgBWhave the effect of anti-inflamation. Moreover, it can be said that the result of this research showed that the dose that has a lower inflamation percent was ES 300 mg/KgBW. Keywords: Anti-inflammation, Hyptis capitata Jacq., Carrageenan, Inflamed Paw Volume.